2015
DOI: 10.1111/fwb.12630
|View full text |Cite
|
Sign up to set email alerts
|

Drought survival strategies, dispersal potential and persistence of invertebrate species in an intermittent stream landscape

Abstract: Summary Intermittent stream systems create a mosaic of aquatic habitat that changes through time, potentially challenging freshwater invertebrate dispersal. Invertebrates inhabiting these mosaics may show stronger dispersal capacity than those in perennial stream systems. To relate different combinations of dispersal and drought survival strategies to species persistence, we compared the distribution and dispersal potential of six invertebrate species across all streams in a montane landscape where drying is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 67 publications
(163 reference statements)
3
38
0
Order By: Relevance
“…The arrival of multiple insect taxa in spring suggested that aerial adults are an important recolonist source in the Lathkill, as in other temporary streams (Robson, Chester & Austin, ; Bogan et al ., ). Their contribution to community resilience is particularly pronounced in catchments, such as the Lathkill, that are hydrologically isolated and/or lack perennial upstream waters (Chester et al ., ). Management strategies and restoration projects seeking to promote invertebrate persistence in headwater streams should therefore look beyond instream conditions and seek to sustain and enhance terrestrial habitats of adult insects (Leigh et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The arrival of multiple insect taxa in spring suggested that aerial adults are an important recolonist source in the Lathkill, as in other temporary streams (Robson, Chester & Austin, ; Bogan et al ., ). Their contribution to community resilience is particularly pronounced in catchments, such as the Lathkill, that are hydrologically isolated and/or lack perennial upstream waters (Chester et al ., ). Management strategies and restoration projects seeking to promote invertebrate persistence in headwater streams should therefore look beyond instream conditions and seek to sustain and enhance terrestrial habitats of adult insects (Leigh et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, for the many actively dispersing, flying adult insects, these small distances are likely to be within their dispersal range (cf. Chester, Miller, Valenzuela, Wickson, & Robson, ; Razeng et al, ). Secondly, heavy wet‐season rainfall causes overland flow across pavements and flow along ephemeral channels connecting rock pools.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an understanding of the ecology, life history and physiological characteristics of these crustaceans is critical, not only to better understand the observed differences in populations structure, but also to predict their future response to climate change. Dispersal capacity alone does not predict persistence, with some invertebrates retaining large local population sizes despite unfavourable conditions and limited dispersal capacity (Davis, Harrington & Friend, 1993;Murphy et al, 2013;Chester et al, 2015).…”
Section: Discussionmentioning
confidence: 99%